The Prohibition of Monosodium Glutamate in Food From the Perspective of Contemporary Fiqh and Health - Nasution, Muhammad Hasan; Irham, Muhammad Iqbal; Hamdani, Muhammad Faisal (STAI Serdang Lubuk Pakam, 2025)
The issue of the halal status of food ingredients, particularly Monosodium Glutamate, has sparked debate among Muslims due to its potential health implications. This study aims to analyze the halal status of Monosodium Glutamate from the perspectives of contemporary Islamic jurisprudence and health. Using a qualitative interdisciplinary approach, this study combines contemporary Islamic jurisprudence and health science to describe the legal status of Monosodium Glutamate and its effects on the body. The results indicate that Monosodium Glutamate can be categorized as haram Lil ghoyrihi (haram due to external effects), specifically its negative impact on health, in accordance with Islamic principles that protect the body and mind. This approach opens a dialogue between scholars and medical authorities and provides a foundation for determining the halal status of food. The implications of this study are the need for a balanced approach between medical considerations and Islamic law in determining the halal status of food ingredients. Public education about the potential health risks of Monosodium Glutamate is important so that Muslims can make wiser decisions regarding food consumption.